An overview on biodegradation of carbamate pesticides by soil bacteria - Mustapha, Mohammed Umar; Halimoon, Normala; Wan Johari, Wan Lutfi; Abd. Shukor, Mohd. Yunus (Universiti Putra Malaysia Press, 2019)
Carbamates are poisonous pesticides which have been used widely in agriculture production for decades. Unlike other pesticides such as organophosphate, carbamate pesticides are not persistent in the environment however, their degradation is crucial due to their toxicity to living system. The World Health Organization, categorized carbamate pesticide as toxic, hazardous and restricted for use. Example of carbamates pesticides include Carbaryl, Aldicarb, Methomyl, Carbofuran, and Propoxur. They are extensively used to control many insect and pests of crops. Presently, there is significant awareness regarding the negative effects of pesticides due to their ability to pollute soil and water bodies. Most pesticides are readily degraded or metabolized by microbes. Carbamate pesticide degradation by microorganisms relies not only on the availability of microbes with suitable biodegradative enzymes, but also on the various ecological factors. This review-article outlines the present development in biodegradation of carbamate pesticides, their toxicity and enzymatic degradation as well as their degradative pathways.